2017
DOI: 10.1007/s10664-016-9493-x
|View full text |Cite
|
Sign up to set email alerts
|

On negative results when using sentiment analysis tools for software engineering research

Abstract: Recent years have seen an increasing attention to social aspects of software engineering, including studies of emotions and sentiments experienced and expressed by the software developers. Most of these studies reuse existing sentiment analysis tools such as SENTISTRENGTH and NLTK. However, these tools have been trained on product reviews and movie reviews and, therefore, their results might not be applicable in the software engineering domain. In this paper we study whether the sentiment analysis tools agree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 81 publications
10
103
0
Order By: Relevance
“…Still, many of these tools have not been designed or trained for handling the technical content typical of the software domain [127]. For instance, Jongeling et al [128] have compared various sentiment analysis tools used in previous studies in software engineering and found that they can disagree with the manual labeling of corpora performed by individuals as well as with each other. Therefore, we advocate caution when drawing conclusions from NLP tools not specifically trained for the specific purpose and lexicon, and we acknowledge this as a potential threat to instrumentation validity.…”
Section: Limitationsmentioning
confidence: 99%
“…Still, many of these tools have not been designed or trained for handling the technical content typical of the software domain [127]. For instance, Jongeling et al [128] have compared various sentiment analysis tools used in previous studies in software engineering and found that they can disagree with the manual labeling of corpora performed by individuals as well as with each other. Therefore, we advocate caution when drawing conclusions from NLP tools not specifically trained for the specific purpose and lexicon, and we acknowledge this as a potential threat to instrumentation validity.…”
Section: Limitationsmentioning
confidence: 99%
“…However, some researchers noticed unreliable results when directly employing such tools for SE tasks [38,41]. Jongeling et al [38] observed the disagreement among these existing tools on the datasets in SE and found that the results of several SE studies involving these sentiment analysis tools cannot be confirmed when a different tool is used. To investigate the challenges in sentiment analysis in SE, Islam and Zibran [35] applied the most popular SentiStrength to some labeled issue comments extracted from JIRA issue tracking system and conducted an indepth qualitative study to uncover twelve difficulties in identifying the sentiments of SE-related texts by analyzing the misclassified samples.…”
Section: Sentiment Analysis In Sementioning
confidence: 99%
“…Previous studies found that sentiment analysis tools trained on non-technical texts are not adequate for SE tasks [35,38] and a lack of domain-specific knowledge is the main reason [35]. Since then, many studies focused on how to use labeled SE-related texts to train SE-customized sentiment classifiers [8,14,35].…”
Section: Lessons Learned and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the poor accuracy of existing sentiment analysis tools trained with general sentiment expressions [4], recent studies have tried to customize such tools with software engineering datasets [5]. However, it is reported that no tool is ready to accurately classify sentences to negative, neutral, or positive, even if tools are specifically customized for certain software engineering tasks [5].…”
Section: Introductionmentioning
confidence: 99%